2021
DOI: 10.1186/s12903-021-01419-0
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between oral health-related knowledge, attitudes, practice, self-rated oral health and oral health-related quality of life among Chinese college students: a structural equation modeling approach

Abstract: Background This study aimed to evaluate the associations among oral health-related knowledge, attitudes, practice (KAP), self-rated oral health and oral health-related quality of life (OHRQoL) among Chinese college students. Methods Of the 2000 participants, 1751 (87.55%) students answered an online questionnaire between October 2019 and January 2020. The questionnaire included demographic characteristics, knowledge, attitudes, and practice related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 58 publications
(31 reference statements)
1
43
1
1
Order By: Relevance
“…A survey showed that 60% of the participants agreed that their delayed help seeking was caused by a lack of knowledge about mental health problems. The theory of knowledge–attitude–practice (KAP) revealed that healthy knowledge is an important basis for developing positive attitudes and further promoting behavior change ( 45 ). People with poor MHL may lead to increased stigma about mental illness ( 46 ).…”
Section: Introductionmentioning
confidence: 99%
“…A survey showed that 60% of the participants agreed that their delayed help seeking was caused by a lack of knowledge about mental health problems. The theory of knowledge–attitude–practice (KAP) revealed that healthy knowledge is an important basis for developing positive attitudes and further promoting behavior change ( 45 ). People with poor MHL may lead to increased stigma about mental illness ( 46 ).…”
Section: Introductionmentioning
confidence: 99%
“… 2 3 Furthermore, oral health is an important indicator of the overall health and well-being, as well as the quality of life. 4 The most common problems seen in the oral cavity are tooth decay (caries), periodontal diseases, and oral carcinoma. One investigation found that oral diseases were present in 3.9 billion people in the world and were led by tooth decay.…”
Section: Introductionmentioning
confidence: 99%
“…Food rich in carbohydrates, tobacco, and alcohol consumption; poor oral hygiene and inadequate dental maintenance contribute to the development of oral diseases. 4 6 7 Behavior is defined as a constant and usual mode of carrying out something or behaving and is extremely hard to give up, while the attitude is defined as the way in which a person views and evaluates something or someone. Attitude determines our tendencies of behaving in a certain way.…”
Section: Introductionmentioning
confidence: 99%
“…Dental caries and periodontal disease and the probable consequences of both (tooth loss) are serious dental public health issues that affect people all over the world [ 6 , 21 , 46 ]. Individuals’ quality of life and general health are negatively impacted by poor oral health and untreated oral illnesses [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oral and orofacial problems can affect children and adolescents, affecting physical functioning and psychosocial well-being [ 6 ]. One of the scientific theories used to influence human health-related behaviors is the knowledge, attitude, and practices (KAP) theory.…”
Section: Introductionmentioning
confidence: 99%